Exploring Turkish Pre-Service Teachers' Perceptions and Views of Digital Literacy - Rıdvan Ata; Kasım Yıldırım (MDPI AG, 2019)
This study aims to investigate digital literacy perceptions of preservice teachers, and to identify quantity characteristics of first and second year preservice teachers’ digital literacy at a public university in Turkey. That is, pre-service teachers’ perceptions of digital literacy and their patterns of knowledge and use of digital literacy were measured within the scope of this study. Multiple sources of data, including a Likert scale and open-ended questions were collected to address the topic. Various statistical techniques and tests such as ANOVA, t-test, and Tukey HSD test were used in the analysis of the obtained data. Qualitative data was analyzed by using the content analysis method. The findings indicated that the model showed a good fit with the data and standardized regression weights indicated that attitude, technical, cognitive, and social factors were significant predictors of digital literacy. In addition, it was identified that the pre-service teachers had high and positive perceptions of digital literacy. However, it was observed in the open-ended questions that they lack the refined cognitive skills to find, evaluate, create, and communicate. The findings were then discussed in light of the relevant literature.